Assessment of Sentinel-1 C-band SAR snow depth assimilation in operational hydrological modeling of high-alpine catchments - T. Pulka-Petzolt; C. Ehrendorfer; H. Lievens; F. Koch; K. Schulz; H. Formayer; F. Avanzi; M. Girotto; M. Herrnegger (Journal of Hydrology, 2026)

Correction to: Functional redundant soil fauna and microbial groups and processes were fairly resistant to drought in an agroecosystem - A. Watzinger; J. Prommer; A. Spiridon; W. Kisielinska; R. Hood-Nowotny; S. Leitner; W. Wanek; C. Resch; M. Heiling; E. Murer; H. Formayer; A. Wawra; et al. (Biology and Fertility of Soils, 2023)

Functional redundant soil fauna and microbial groups and processes were fairly resistant to drought in an agroecosystem - A. Watzinger; J. Prommer; A. Spiridon; W. Kisielinska; R. Hood-Nowotny; S. Leitner; W. Wanek; C. Resch; M. Heiling; E. Murer; H. Formayer; A. Wawra; et al. (Biology and Fertility of Soils, 2023)
Climate change scenarios predict more frequent and intense drought periods for 2071 to 2100 for many regions of the world including Austria. Current and predicted lower precipitation scenarios were simulated at a lysimeter station containing a fertile and less fertile agricultural soil for 9 years. 13 C and 15 N-labeled green manure was added in year 8 with the aim to analyze how the predicted precipitation regime affects soil fauna and microbial groups and consequently nitrogen (N) and carbon (C) cycling. Among the investigated mesofauna (collembola and oribatida), the abundance and biodiversity of oribatida was significantly reduced by drought, possibly because they mainly represent K-strategist species with low mobility and consequently the need to adapt to long-term adverse environmental conditions. Microbial community composition and microbial biomass, investigated by phospholipid fatty acid (PLFA) analysis, was indistinguishable between the current and the predicted precipitation scenarios. Nonetheless, soil 13 C-CO 2 emissions and soil water 15 N-NO 3 data revealed decelerated mineralization of green manure under reduced precipitation in the first 2 weeks, but no effects were observed on soil C sequestration or on 13 C incorporation into microbial PLFAs in the following 1.2 years. We found that over a 1-year time period, decomposition was rather driven by plant residue availability than water limitation of microorganisms in the investigated agroecosystem. In contrast, N 2 O emissions were significantly reduced under drought, and green manure derived 15 N accumulated in the soil under drought, which might necessitate the adjustment of future fertilization regimes. The impacts of reduced precipitation and drought were less pronounced in the more fertile agricultural soil, due to its greater buffering capacity in terms of water storage and organic matter and nutrient availability.

Cutoff low systems and their relevance to large-scale extreme precipitation in the European Alps - N. K. Awan; H. Formayer (Theoretical and Applied Climatology, 2017)

High resolution climate data for Austria in the period 2008–2040 from a statistical climate change model - F. Strauss; H. Formayer; E. Schmid (International Journal of Climatology, 2013)
Climate change data for Austria have been produced for the period from 2008 to 2040, with a temporal/spatial resolution of 1 d and 1 km 2 . The climate change data are based on historical daily weather station data from 1975 to 2007, and linear regression modelling with repeated bootstrapping. The spatial resolution is based on 60 climate clusters which represent homogenous climates with respect to mean annual precipitation sums and mean annual temperatures from the period 1961 to 1990. For each climate cluster, a regression model fit has been performed and extrapolated for the period 2008–2040. The integral parts of our regression model are: (1) the extrapolation of the observed linear temperature trend from 1975 to 2007, by using an average national trend of approximately 0.05 °C per year derived from a homogenized dataset, and (2) the repeated bootstrapping of historical temperature residuals, and of the observations for some other weather parameters, such as solar radiation, precipitation, relative humidity and wind speed. Thus, we ensure consistent physical, spatial and temporal correlations. Precipitation scenarios have been developed to account for any possible wider range of precipitation patterns. These scenarios include increased/decreased annual precipitation sums, as well as unchanged annual precipitation sums, but with different seasonal distributions. These climate change data are available at: http://www.landnutzung.at/Klima_Daten.html Copyright © 2012 Royal Meteorological Society

Synoptic and regional patterns of heavy precipitation in Austria - P. Seibert; A. Frank; H. Formayer (Theoretical and Applied Climatology, 2007)